54.5k views
3 votes
Solve: x + 3 = –x + 7

User Jysummers
by
6.4k points

2 Answers

2 votes

Answer:

x = 2

Explanation:

x+3 = -x + 7

x = -x + 4

(2) = -(2) + 4

2 = 2

User Rajvijay
by
5.8k points
3 votes

Answer:

The correct answer is x = 2.

Explanation:

To solve this equation, we must get all of the variables (x's) to one side of the equation and get all of the constant terms (numbers only) to the other side.

Starting with this equation, we are going to add x to both sides of the equation. This will cancel out the -x on the right side of the equation, thereby moving all of the variable x's to the left side of the equation.

x + x + 3 = -x + x + 7

If we simplify by combining like terms, or adding the x's together, we get:

2x + 3 = 7

Next, we should subtract 3 from both sides of the equation in order to move all of the constant terms to the right side of the equation.

2x + 3 -3 = 7 - 3

If we simplify, we get:

2x = 4

Finally, we should divide both sides by 2 in order to get the variable x alone on the left side of the equation, solving it.

x = 2

Therefore, your answer is x = 2.

Hope this helps!

User Sum None
by
5.9k points